On the dimensions of certain spaces of vector-valued cusp forms: On the dimensions of certain spaces of vector-valued cusp forms - Nasit, Darshan (The Ramanujan journal, 2025)
Given an irreducible representation of SL 2 ( F q ) for an odd prime q , we find the dimension of the space of cusp forms with respect to the full modular group taking values in the representation space. The dimension equals the multiplicity of the representation in the space of classical cusp forms with respect to the principal congruence subgroup of level q .